Kualitas Telur Itik Alabio (Anas platyrhynchos Borneo) yang Dipengaruhi oleh Variasi Induk Umur 7 dan 10 Bulan - Muttaqin, Gusti Zainal; Rizal, Muhammad; Biyatmoko, d (www.ulm.ac.id, 2025)
This study aims to determine the effect of different duck production age variations on externalegg quality, namely egg shape index, egg weight, and shell thickness and internal egg quality,namely haugh unit, yolk index, egg white index, and yolk color in Alabio duck eggs. The researchwas conducted for 2 months starting in October to November 2023. The research was conductedat the Animal Nutrition and Diet Laboratory of the Department of Animal Husbandry, Faculty ofAgriculture, ULM. The method used in this research is quantitative observation method throughmeasurement of egg shape index part, egg weight, shell thickness, haugh unit, egg white index,yolk index, yolk color. This study used 2 groups of duck parent populations with different ages,the first group of 7-month parent age and the second group of 10-month parent age. The dataobtained were analyzed descriptively, and to see the difference in duck age on the observed qualityvariables, a t-test of each research variable was carried out. The results showed that age had asignificant effect on egg shape index, egg weight, shell thickness, and yolk index. But age had nosignificant effect on haugh unit, egg white index, and egg yolk color. In testing using SPSS therewas an increase in egg shape index, egg weight, shell thickness, and yolk index. Except for thehaugh unit and egg white index decreased. The yolk color had the same value.